Burnout, Depression, Anxiety, and Stress Among Resident Physicians 18 Months into the COVID-19 Pandemic: A Cross-Sectional Study - Ofei-Dodoo, Samuel; Irwin, Gretchen; Wright, Brynn; Krohn, Kimberly; Williams, Kimberly; Dooley, Philip; Duggins, Maurice (Kansas Journal of Medicine, 2022)
INTRODUCTION. Burnout among resident physicians has been an area of concern that predates the COVID-19 pandemic. With the significant turmoil during the pandemic, this study examined resident physicians’ burnout, depression, anxiety, and stress as well as the benefits of engaging in activities related to wellness, mindfulness, or mental wellbeing. METHODS. The authors conducted a cross-sectional survey of 298 residents from 13 residency programs sponsored by the University of Kansas School of Medicine-Wichita, in October and November 2021. Authors used a 31-item questionnaire to measure levels of burnout, depression, anxiety, and stress. A mixed method approach was used to collect, analyze, and interpret the data. Descriptive statistics, One-way ANOVA/Kruskal-Wallis tests, adjusted odds ratios (aOR), and immersion-crystallization methods were used to analyze the data. RESULTS. There was a 52% response rate, with 65.8% (n=102) of the respondents reporting manifestations of burnout. Those who reported at least one manifestation of burnout experienced a higher level of emotional exhaustion (aOR=6.73; 95% CI, 2.66-16.99; P<.01), depression (aOR=1.21; 95% CI, 1.04-1.41; P=.01), anxiety (aOR=1.14; 95% CI, 1.00-1.30; P=.04), and stress (aOR=1.36; 95% CI, 1.13-1.64; P<.01). Some wellness activities respondents engaged in included regular physical activities, meditation and yoga, support from family and friends, religious activities, time away from work, and counseling sessions. CONCLUSIONS. The findings suggest the COVID-19 pandemic continues to pose a significant and worsening prevalence of burnout and other negative mental health effects on residents. Appropriate wellness and mental health support initiatives are needed to help resident physicians thrive in the health care environment.